Validation of a Bioanalytical Method for the Determination of Synthetic and Natural Cannabinoids (New Psychoactive Substances) in Oral Fluid Samples by Means of HPLC-MS/MS - Calò, Luca; Anzillotti, Luca; Maccari, Chiara; Cecchi, Rossana; Andreoli, Roberta (Frontiers in Chemistry, 2020)
New psychoactive substances (NPS) represent an important focus nowadays and are continually produced with minimal structural modifications in order to circumvent the law and increase the difficulty to identify them. Moreover, since the high number of different compounds, it is arduous to develop analytical screening and/or confirmation methods that allow the identification and quantification of these compounds. The aim of this work is to develop and validate a bioanalytical method to detect new synthetic drugs in biological samples, using high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS/MS) in oral fluid with minimal sample pretreatment. Oral fluid samples were simply centrifuged and denaturised with different quick procedures before injection in LC-MS/MS system. Calibration curves covered a linear concentration range of 0-100 ng/mL. Validation parameters such as linearity, precision, accuracy, selectivity, matrix effect and thermal stability were evaluated and showed satisfactory results, in accordance with the US Food & Drug Administration guidelines. Inter-day analytical bias and imprecision at two levels of quality control (QC) was within ±15%. This method was able to identify and calculate the concentration of 10 NPS validated in this biological sample, even in presence of matrix effect.